1991
DOI: 10.1116/1.577267
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stress-induced and electromigration-induced void-open failures in Al and Al–Cu fine lines

Abstract: Articles you may be interested inStress-induced and electromigration voiding in nitride passivated Al interconnects AIP Conf. Proc. 491, 174 (1999); 10.1063/1.59906In situ transmission electron microscopy study of plastic deformation and stress-induced voiding in Al-Cu interconnects

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The effects rather than vacancy relaxation effects. Finally, the measurements to date have been limited to moderate frequencies deviation in lifetime from the expected current density (<10 MHz) with the exception of Kwok et al [3], who extended dependence, characterized over IY2 orders of magnitude in the range to 200MHz. Unfortunately, their lowest frequency current density, is explained in terms of a shift in the boundary was 50 MHz, which makes it difficult to compare that work to condition for electromigration as the current density is decreased, other studies.…”
mentioning
confidence: 99%
“…The effects rather than vacancy relaxation effects. Finally, the measurements to date have been limited to moderate frequencies deviation in lifetime from the expected current density (<10 MHz) with the exception of Kwok et al [3], who extended dependence, characterized over IY2 orders of magnitude in the range to 200MHz. Unfortunately, their lowest frequency current density, is explained in terms of a shift in the boundary was 50 MHz, which makes it difficult to compare that work to condition for electromigration as the current density is decreased, other studies.…”
mentioning
confidence: 99%
“…Since 1984 it has been observed that voids form in A1 interconnects under a passivation layer, even under zero current density [168][169][170][171][172][173][174][175][176][177][178]. Since there is mechanlcal constraint in unpassivated interconnects, no stress voiding has been reported so far in the unpassivated lines.…”
Section: B2 Stress Induced Voiding In A1 Interconnectsmentioning
confidence: 99%
“…Recently such a relationship has been suggested from results of cxperiments appearing in the literature. [6,7] History During a pre-qualification investigation of a new multi-level metal process, erratic electromigration performance was discovered during the testing of metal at the second level. In many cases, second metal (M2) performed below requirements, whereas first level metal (Ml) and third level metal (M3) were quite satisfactoiy even though the metal systems were similar.…”
Section: Introductionmentioning
confidence: 99%